Prolyl oligopeptidase inhibition by KYP-2407 increases alpha-synuclein fibril degradation in neuron-like cells - Jinar Rostami; Maria Jäntti; Hengjing Cui; Maiju K. Rinne; Jyrki P. Kukkonen; Anna Falk; Anna Erlandsson; Timo Myöhänen (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2022)
Growing evidence emphasizes insufficient clearance of pathological alpha-synuclein (alpha SYN) aggregates in the progression of Parkinson's disease (PD). Consequently, cellular degradation pathways represent a potential therapeutic target. Prolyl oligopeptidase (PREP) is highly expressed in the brain and has been suggested to increase alpha SYN aggregation and negatively regulate the autophagy pathway. Inhibition of PREP with a small molecule inhibitor, KYP-2407, stimulates autophagy and reduces the oligomeric species of alpha SYN aggregates in PD mouse models. However, whether PREP inhibition has any effects on intracellular alpha SYN fibrils has not been studied before. In this study, the effect of KYP2407 on alpha SYN preformed fibrils (PFFs) was tested in SH-SY5Y cells and human astmcytes. Immunostaining analysis revealed that both cell types accumulated alpha SYN PFFs intracellularly but KYP-2047 decreased intracellular alpha SYN deposits only in SH-SY5Y cells, as astrocytes did not show any PREP activity. Western blot analysis confirmed the reduction of high molecular weight alpha SYN species in SH-SY5Y cell lysates, and secretion of aSYN from SH-SY5Y cells also decreased in the presence of KYP-2407. Accumulation of alpha SYN inside the SH-SY5Y cells resulted in an increase of the auto-lysosomal proteins p62 and LC3BII, as well as calpain 1 and 2, which have been shown to be associated with PD pathology. Notably, treatment with KYP-2407 significantly reduced p62 and LC3BII levels, indicating an increased autophagic flux, and calpain 1 and 2 levels returned to normal in the presence of KYP-2407. Our findings indicate that PREP inhibition can potentially be used as therapy to reduce the insoluble intracellular alpha SYN aggregates.